2006
DOI: 10.1029/2006gl026561
|View full text |Cite
|
Sign up to set email alerts
|

Satellite‐based assessment of possible dust aerosols semi‐direct effect on cloud water path over East Asia

Abstract: [1] The semi-direct effects of dust aerosols are analyzed over eastern Asia using 2 years (June 2002 to June 2004 The results show that the water path of dust-contaminated clouds is considerably smaller than that of dust-free clouds. The mean ice water path (IWP) and liquid water path (LWP) of dusty clouds are less than their dust-free counterparts by 23.7% and 49.8%, respectively. The long-term statistical relationship derived from ISCCP also confirms that there is significant negative correlation between du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
163
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 268 publications
(168 citation statements)
references
References 26 publications
2
163
0
3
Order By: Relevance
“…Multiza et al (2010) found that local anthropogenic dust aerosols associated with human activities such as agriculture and industrial activity accounted for 43 % of the total dust burden in the atmosphere. Analysis of satellite observations indicated that, on average, both naturally transported and local anthropogenic dust aerosols can significantly reduce water cloud particle size, optical depth, and liquid water path (Huang et al, 2006a(Huang et al, , b, 2010. These results suggest that dust aerosols warm the clouds and increase evaporation of cloud droplets, further reducing cloud water path via the so-called semi-direct effect.…”
Section: Discussionmentioning
confidence: 89%
“…Multiza et al (2010) found that local anthropogenic dust aerosols associated with human activities such as agriculture and industrial activity accounted for 43 % of the total dust burden in the atmosphere. Analysis of satellite observations indicated that, on average, both naturally transported and local anthropogenic dust aerosols can significantly reduce water cloud particle size, optical depth, and liquid water path (Huang et al, 2006a(Huang et al, , b, 2010. These results suggest that dust aerosols warm the clouds and increase evaporation of cloud droplets, further reducing cloud water path via the so-called semi-direct effect.…”
Section: Discussionmentioning
confidence: 89%
“…However, the semidirect effect has the potential to offset this cooling by reducing low cloud cover and water path. Analysis of the satellite observations indicates that, on average, the water path of dusty clouds is considerably smaller than that from dustfree clouds in the same frontal systems (Huang et al, 2006a, b). The absorption or diabatic heating of Asian dust particles can cause the evaporation of cloud droplets and reduce the cloud water path.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, special attention has been dedicated to cloud interactions with desert aerosol particles (Rosenfeld et al, 2001;Bréon et al, 2002;DeMott et al, 2003;Kawamoto and Nakajima, 2003;Huang et al, 2006a, b). However, the knowledge of the effects of Asian dust aerosols on arid climate is still very limited due to the lack of observations.…”
Section: Introductionmentioning
confidence: 99%
“…Long-range transport of Asian dust is one of the important sources of atmospheric aerosols in the downwind regions, particularly during the dust seasons. Asian dusts can influence ecosystems, environments, and climates (Sokolik and Toon, 1996;Sokolik et al, 2001;Han et al, 2004;Cao et al, 2005;Huang et al, 2006bHuang et al, , 2008. Some Asian dust may settle on the ocean's surface and provide nutrients (e.g., Fe 2+ ) to the oceanic biosphere (Zhuang et al, 1992).…”
Section: Introductionmentioning
confidence: 99%